The Relationship Between Religiosity and Self-Control with Online Gambling Addiction in Online Gamblers - Billah, Muhammad Asyiiq; Sofiah, Diah; Arifiana, Isrida Yul (Kirana Publisher (KNPub), 2025)
This study aims to determine the relationship between religiosity and self-control on online gambling addiction in online gamblers. Addiction is a psychological problem that the sufferer does not directly realise. So, sometimes, it causes online gamblers not to understand or even recognise. Online gambling addiction is a serious problem. Someone who is addicted cannot control their desire to bet. In addition, taking risky actions such as increasing the amount of bets, playing without knowing the time, not limiting the amount of money spent on playing, and causing other social problems. The research method used is quantitative correlation with a sample of 141 online gamblers. With a sampling technique using accidental sampling. The data collection instrument uses three scales: the online gambling addiction scale, the religiosity scale and the self-control scale. Data analysis was conducted using validity, reliability tests, and multiple regression analysis. Based on the results of the study show a significant negative relationship between religiosity and online gambling addiction (p = 0.000 (p < 0.05). And between self-control and online gambling addiction (p = 0.000, p < 0.05). Multiple regression analysis also shows a significant relationship between religiosity and self-control with online gambling addiction. This means that there is a significant correlation between religiosity and self-control with online gambling addiction. This shows that the lower the religiosity and self-control can affect the higher online gambling addiction in online gamblers.